Netizen Reactions to the Viral Phenomenon of “Tabola Bale”: A Digital Humanities Approach Using Voyant Tools - Aura Prisca Medina; Filosa Gita Sukmono (CommLine, 2026)
The development of new media has positioned the audience as active producers of meaning, where the TikTok comment section functions as a primary arena for identity negotiation and participatory culture. This article examines the viral phenomenon of the song "Tabola Bale," focusing on the dynamics of digital crowd interaction in responding to the trend. This study aims to dissect the narrative structure, emotional patterns, and social construction formed behind thousands of netizen comments. The method used is qualitative with a Digital Humanities approach, utilizing the corpus linguistics software Voyant Tools to visualize data through Cirrus, Trends, and ScatterPlot features. The results indicate that the virality of "Tabola Bale" is constructed through three main dimensions. First, high emotional intensity and social conformity, characterized by the dominance of intensifier lexicons such as "banget" (very) and "candu" (addicted). Second, the operation of identity politics and participatory culture, where the words "timur" (East Indonesia) and "dance" appear consistently as forms of local cultural pride and performative bodily participation. Third, the existence of a transnational virality dimension revealed through the clustering of English words and references to "Philippines," signaling cross-border cultural exchange despite the occurrence of meaning desemantization. In conclusion, the TikTok comment section is not merely a review space, but an arena for constructing social reality where emotional validation, local identity, and global interaction intertwine to form popular culture trends.